Identification of MHCII variants associated with chlamydial disease in the koala (Phascolarctos cinereus) - Lau, Quintin; Griffith, Joanna E.; Higgins, Damien P. (PeerJ, 2014)
Chlamydiosis, the most common infectious disease in koalas, can cause chronic urogenital tract fibrosis and infertility. High titres of serum immunoglobulin G against 10 kDa and 60 kDa chlamydial heat-shock proteins (c-hsp10 and c-hsp60) are associated with fibrous occlusion of the koala uterus and uterine tube. Murine and human studies have identified associations between specific major histocompatibility complex class II (MHCII) alleles or genotypes, and higher c-hsp 60 antibody levels or chlamydia-associated disease and infertility. In this study, we characterised partial MHCII DAB and DBB genes in female koalas (n = 94) from a single geographic population, and investigated associations among antibody responses to c-hsp60 quantified by ELISA, susceptibility to chlamydial infection, or age. The identification of three candidate MHCII variants provides additional support for the functional role of MHCII in the koala, and will inform more focused future studies. This is the first study to investigate an association between MHC genes with chlamydial pathogenesis in a non-model, free-ranging species.
Keywords: Marsupial; Immunology; MHC; Chlamydia; Disease; Major histocompatibility complex; Koala; Heat shock proteins